THE EFFECT OF DISCOUNTS, ELECTRONIC WORD OF MOUTH (EWOM), AND PRICE TOWARDS INTEREST IN BUYING IN E-COMMERCE - Setiawan, Adam; Putri, Yesi Septia (FEBI UIN Sunan Kalijaga, 2020)
The purpose of this study was to determine whether the Discounted Price, Electronic Word of Mouth, and Price affect the Purchase Interest of UIN Sunan Kalijaga Yogyakarta Students in Shopee E-Commerce. The population used is the students of UIN Sunan Kalijaga Yogyakarta. The number of samples in this study were 100 students of UIN Sunan Kallijaga Yogyakrata. This study uses primary data analysis method used is multiple linear regression analysis using SPSS version 23. The results of this study indicate that Discounted Price has a positive and significant effect on Purchasing Interest, Electrnic Word of Mouth has a positive and significant effect on Consumer Purchase Interest, Word of Mouth has a significant effect on Purchase Interest and Harag has a positive and significant effect on Buy Interest. Together, Discounts, Electronic Word of Mouth and Prices have a positive and significant effect on the Purchasing Interest of UIN Sunan Kaljaga Yogyakarta Students in E-Commerce Shopee. Companies should develop a Discount, Electronic Word of Mouth and Price strategy with the hope of increasing consumer Purchase Interest and can be used as a reference for the development and deepening of marketing management knowledge of FEBI UIN Sunan Kalijaga students